Multiscale Asymptotic Expansion for a Class of Hyperbolic-Parabolic Type Equation with Highly Oscillatory Coefficients (Journal of Computational Mathematics, 2002)
In this paper, we will discuss the asymptotic behaviour for a class of hyperbolic-parabolic type equation with highly oscillatory coefficients arising from the strong-transient heat and mass transfer problems of composite media. A complete multiscale asymptotic expansion and its rigorous verification will be reported.